The Priority of Intention and Charity in Hadith Qudsi: Study of Sahih Bukhari - Almara Sukma; Tasniatul Karimah; Khamim Khamim (Penerbit Hellow Pustaka, 2026)
This study examines the hadith qudsi in Sahih Bukhari, which explains the virtue of intention, deed, and how to draw closer to Allah SWT. The phenomenon demonstrated that the desire to perform good deeds is often hampered by various factors, necessitating a comprehensive understanding of the value of intention and deed in Islam. This study aims to motivate and provide understanding to Muslims to remain consistent in performing good deeds and strengthen their spiritual closeness to Allah SWT. The method used is library research with a descriptive-analytical approach. The primary source in this study is the book Qawā‘id al-Taḥdīṡ, while secondary sources include books of hadith, hadith commentaries, books, and relevant journal articles. The results of the study indicate that the first hadith emphasizes the urgency of intention in every deed, where good intentions that have not been realized are still recorded as rewards, good deeds performed are multiplied in reward, and bad intentions abandoned out of fear of Allah SWT are considered good. Conversely, bad intentions abandoned for reasons other than Allah are still recorded as bad. The second hadith emphasizes that obligatory deeds are the deeds most loved by Allah SWT and are the main foundation for getting closer to Him, while sunnah deeds function as perfection that leads a servant to the love of Allah SWT. Thus, both hadith provide important guidelines on the priority of improving intentions, consistency in carrying out obligatory worship, and increasing sunnah deeds as an effort to gain the pleasure, love, and protection of Allah SWT.